(untitled) (LIS TODAY, 2024)
Persistent identifiers (PIDs) are essential for information access and resource discovery in scientific journal management systems. It provides a unique and permanent reference identification number for digital objects, enabling researchers to locate access quickly and cite the data. The names of various persistent identifiers (PIDs) are Archival Resource Key (ARK), Digital Object Identifier (DOI), Handle System, and Persistent Uniform Resource Locator (PURL). This article deals with PIDs’ characteristics and power, enabling data sharing, collaboration, and advancing research. The paper also discusses PIDs’ benefits, applications, and future direction. Uses of persistent identifiers transform the impact of the research landscape.